2007
DOI: 10.1007/s10526-007-9075-3
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of the predatory stinkbug Picromerus bidens to selected insecticides

Abstract: The Palaearctic stinkbug Picromerus bidens L. (Heteroptera: Pentatomidae) has been considered as a potential biocontrol agent of several defoliator pests in various agricultural and forest ecosystems. It may therefore be a valuable alternative for the Nearctic pentatomid Podisus maculiventris (Say) (Heteroptera: Pentatomidae), the augmentative use of which has largely been abandoned in Europe given its possible environmental impact as an exotic polyphagous predator. However, no study has yet documented the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 32 publications
2
15
0
3
Order By: Relevance
“…Kamminga et al (2009) reported that spinosad was as effective as lambda-cyhalothrin in laboratory bioassays against C. hilaris and E. servus. Spinosad was also promising against H. halys in our studies, and this material has demonstrated selectivity against the predatory stink bug, Picromerus bidens (L.) (Mahdian et al 2007).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Kamminga et al (2009) reported that spinosad was as effective as lambda-cyhalothrin in laboratory bioassays against C. hilaris and E. servus. Spinosad was also promising against H. halys in our studies, and this material has demonstrated selectivity against the predatory stink bug, Picromerus bidens (L.) (Mahdian et al 2007).…”
Section: Discussionmentioning
confidence: 65%
“…Organic insecticides may also continue being used in conjunction with other management tactics. To date, very little is known regarding the efficacy of insecticidal materials approved for use in organic farming against H. halys and fewer organic insecticides are available compared with conventional insecticides that have proven effective against other pentatomids (Durmusoglu et al 2003;Trdan et al 2006;Mahdian et al 2007;Kamminga et al 2009). …”
Section: Impact Of Organic Insecticides On the Survivorship And Mobilmentioning
confidence: 99%
“…In our study, it caused almost 10% mortality. Its residues were not toxic to Orius bugs (Studebaker and Kring 2003) or Picromerus bugs (Mahdian et al 2007), but reduced the fecundity and slowed the development of Deraeocoris bugs (Kim et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…It was found to be toxic to heteropterans (Studebaker and Kring 2003;Myers et al 2006), some hymenopteran parasitoids (Nowak et al 2001), staphylinid beetles, and earwigs (Cisneros et al 2002). It has, however, little negative effect on the survival or reproduction of predatory mites, Harmonia coccinellids (Musser and Shelton 2003), Deraeocoris bugs (Kim et al 2006), Picromerus bugs (Mahdian et al 2007), and braconid wasps (Vargas et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…When ingested or topically applied to an insect, spinosad acts on the nicotinic acetylcholine and GABA receptors (Watson 2001). While spinosad is active against a wide range of insect pests (Thompson et al 1997), it appears to be harmless to mammals and predatory insects (Madhian et al 2007). …”
Section: Introductionmentioning
confidence: 99%